Influence of Maternal Immunization with Allergens on the Thymic Maturation of Lymphocytes with Regulatory Potential in Children: A Broad Field for Further Exploration - Jefferson Russo Victor (Journal of Immunology Research)
A variety of mechanisms are involved in the regulation of offspring allergy development through maternal immunization with allergens. The passive transfer of antigens, antibodies, and cytokines, the induction of phenotypic alterations in offspring lymphocytes, and the induction of regulatory populations in offspring have been proposed, but these mechanisms remain incompletely understood. It is likely that maternal immunization could affect the intrathymic maturation of offspring TCD4+, TCD8+, γδT, nTreg, iNKT, and B lymphocytes, although there are currently no human maternal immunization protocols for the regulation of allergic responses in children. Some studies have suggested a direct interaction between the maternal immune status and the offspring intrathymic microenvironment; this interaction could influence the maturation of offspring regulatory cells and must be explored for the development of therapies to control allergy development in children.